The Cultural Values as Represented in the Indonesian Autism EFL Textbook: Critial Discourse Analysis - Nur Alfin Karimah; Trishna Nanda Barianty (Institut Agama Islam Negeri Palopo, 2022)
Culture is an inseparable aspect when an individual learns a target language. English textbook, one of the teaching-learning media, keeps a lot of hidden cultural value inside. There is a limited study investigating the representation of cultural values in an English textbook for autism students. Thus, this study is addressed to investigate both cultural representation and cultural values inside the Indonesian autism EFL textbook published by the Ministry of Education and Culture. The analysis adopted the four dimensions of culture or 4Ps as the framework. The 4Ps refer to Product, Practice, Perspective, and People. The findings of this study underscore the multicultural values represented in the autism English textbook. Those cultural values are as follows: (1) respecting the diversity of a religious group; (2) respecting the Indonesian national cultural traits; (3) respecting the diversity of ethnic groups; (4) respecting democracy; (5) having good manners; and (6) having gratitude. Recommendation for teacher or professional researcher of research and development closes the section of this study and deepened on the semiotics contained in the English textbook for children with autism and the potential theoretical which can be obtained through the analysis of the intercultural language used in the English textbook.